2019
DOI: 10.1016/j.yexcr.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile of TGF-β1 treated lung fibroblasts identifies novel markers of activated fibroblasts in the silica exposed rat lung

Abstract: We performed liquid chromatography-tandem mass spectrometry (LC-MS/MS) on control and TGF-β1-exposed rat lung fibroblasts to identify proteins differentially expressed between cell populations. A total of 1648 proteins were found to be differentially expressed in response to TGF-β1 treatment and 196 proteins were expressed at ≥ 1.2 fold relative to control. Guided by these results, we next determined whether similar changes in protein expression were detectable in the rat lung after chronic exposure to silica … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Moreover, we also found that PM2.5 promoted the secretion of IL‐17A, activated the TGF signalling pathway and promoted EMT in bronchial epithelial cells, thereby leading to pulmonary fibrosis. In agreement with our results, previous reports have also found IL‐17A to be closely related with pulmonary fibrosis‐related signalling pathways 27‐32 . Moreover, the role of TGF‐β is well known in migration, invasion as well as hyperplastic changes of lung fibroblasts in pulmonary fibrosis 28,33,34 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we also found that PM2.5 promoted the secretion of IL‐17A, activated the TGF signalling pathway and promoted EMT in bronchial epithelial cells, thereby leading to pulmonary fibrosis. In agreement with our results, previous reports have also found IL‐17A to be closely related with pulmonary fibrosis‐related signalling pathways 27‐32 . Moreover, the role of TGF‐β is well known in migration, invasion as well as hyperplastic changes of lung fibroblasts in pulmonary fibrosis 28,33,34 .…”
Section: Discussionsupporting
confidence: 92%
“…The differentiation of fibroblasts to myofibroblasts can be induced by TGF-b1 and is associated with excessive extracellular matrix deposition. 14,15 It has been well documented that serum response factor (SRF) and its transcription cofactor, myocardin-related transcription factor A (MRTF-A), can regulate the expression of a-SMA at the transcriptional level, 16 and they have also been reported to promote the synthesis of collagen type I (Col I) and play a key role in pulmonary fibrosis. 17 In the present study, we found that many of the miRNAs differentially expressed in pulmonary fibrosis had effects on myofibroblast differentiation and the production of extracellular matrix in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of myofibroblasts should be investigated more in detail. According to the pedigree tracing experiment, many kinds of cells in interstitial lung tissue differentiate into myofibroblasts, and their main source is the fibroblast-derived myofibroblasts (Na et al, 2019; Sakai and Tager, 2013). The expression of type I collagen and α-SMA can be detected in fibroblasts when co-cultured with silica-exposed macrophages.…”
Section: Tgf-β1 Induces Fibroblasts To Myofibroblasts Via Paracrinementioning
confidence: 99%